Kredit dalam Islam Berdasarkan Perspektif Hadis - Idris Siregar; Muhammad Rafly; Hairun Sadri (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research aims to examine the principles of credit in Islam based on a hadith perspective. The approach used is a qualitative approach with descriptive-analytic research type. Primary data sources are hadiths related to credit taken from trusted hadith books, such as Sahih Bukhari, Sahih Muslim, Sunan Abu Dawud, and others. Secondary data sources include literature related to hadith interpretation, muamalah fiqh books, academic journals, and scientific articles. Data collection techniques were carried out through literature study and documentation. The research results show that the principles of credit in Islam based on hadith include the prohibition of usury, justice and honesty, and the avoidance of uncertainty (gharar). Apart from that, the hadiths also emphasize the importance of good intentions and benevolence in providing loans and recommend giving concessions or even eliminating debts for those who are unable to pay.